Design Strategies For Low Energy Building Challenge: A Case Study Toward Net Zero Energy Building In UniKL - Mohd Izhar A. Bakar; Mohd Akram Dandu (Journal of Engineering Technology, 2018)
In developed nations, a building itself utilise up to a third of total energy consumption and proper management of energy is vital to offset wastage via utilization of renewable energy generation devices at the building. In line with Malaysia energy policy, the new UniKL’s building will be designed based on Net Zero Energy Building (NZEB) concept [1] . Thus, the point lies in its ability to be self-sufficient with power generated from the own building with Integrated Photovoltaic (BIPV) systems. It is the easiest and most reliable way to get the Net Zero Energy objectives. The NZEB concept consists of orientation on the site, passive and active components so that the total amount of energy used is equal to amount of renewable energy created on the site. Therefore, the propose approaches can improve the energy efficiency on building toward zero Building Energy Index (BEI). Also, this research focuses on how the impact of semi-trans PV on the overall building’s energy performance, taking into account similarities and differences between Conventional PV and Semi-Transparent PV for the use in a NZEB scenario and to achieve zero Net Building Energy Index (NET BEI) without affecting the building occupants thermal and visual comfort and/or imposing operational burdens on the occupants. The analysis and outcome from this paper demonstrates that the building integrate with semi-transparent PV modules contribute to the building’s net zero energy consumption.